Age factors in biometric processing - Fairhurst, Michael 1948- (London, United Kingdom The Institution of Engineering and Technology, 2013)
The book covers the following areas: ageing; biometrics; social considerations; ethical considerations; online signature; fingerprints; human inspection; forensics; face image; age prediction; and face recognition.
Electronic reproduction.
Keywords: Biometric identification -- Age factors; Identification -- Automation; Electronic surveillance; Digital signatures; Human face recognition (Computer science).; Electronic books